Community Empowerment in Managing Household Hazardous Waste in Residential Neighbourhoods - Tantri Wenny Sitanggang; Mila Sari; Kalasta Ayunda Putri; Sandi Setiadi; Eka Cahya Muliawati (CV. Get Press Indonesia, 2024)
This study adopts a mixed-methods approach, combining qualitative and quantitative techniques, to evaluate household hazardous waste management practices. Data were collected through surveys, in-depth interviews, and direct observations. Quantitative data were analyzed using descriptive statistics to measure community awareness levels and the effectiveness of waste management infrastructure, while thematic analysis was applied to qualitative data to identify key issues and patterns in community behavior. The findings highlight the effectiveness of community empowerment programs in improving knowledge and practices, with recognition of hazardous waste types increasing to 85%, understanding of associated hazards to 82%, and a reduction in littering behavior from 65% to 20%. These results underscore the importance of multi-stakeholder collaboration, infrastructure enhancement, and the integration of circular economy principles to achieve sustainable waste management. The study provides actionable, data-driven recommendations for reducing health and environmental risks associated with hazardous waste, emphasizing the need for continuous monitoring and community engagement.